Psychosomatic aspects of a group of health professionals at the Hospital do Agreste during and after the services performed in COVID-19: case series (Research, Society and Development, 2022)
The pandemic is the biggest cause of public health emergency, which brings concerns not only to physical health, as well as psychological suffering to the people affected and the health professionals involved with the moment. Objectives: to evaluate and characterize the quality of life and sleep, symptoms of anxiety and depression in a group of health professionals, through work performance, before and during the COVID-19 pandemic. In addition, to identify the harmful factors that interfere in a negative way in quality of life, sleep, symptoms of anxiety and depression in them. Material and method: Volunteer health professionals will participate in the study. The SF-36 will be used to assess quality of life. The Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality. The Back Anxiety Inventory (BAI) and the Back Depression Inventory (BDI) will be used respectively to assess symptoms of anxiety and depression. The data will be analyzed, with descriptive data of average standard deviation, minimum, maximum and with the size of the effect. Expected results: provide information on the psychosomatic aspects of the health professionals volunteering in the research. Furthermore, pointing out actions and relating effective psychosomatic intervention strategies aimed at improving their well-being.